Structural Elucidation and Activities of Cordyceps militaris-Derived Polysaccharides: A Review - Miao, Miao; Yu, Wen-Qian; Li, Yuan; Sun, Yan-Long; Guo, Shou-Dong (Frontiers in Nutrition, 2022)
Cordyceps militaris is a parasitic edible fungus and has been used as tonics for centuries. Polysaccharides are a major water-soluble component of C. militaris. Recently, C. militaris-derived polysaccharides have been given much attention due to their various actions including antioxidant, anti-inflammatory, anti-tumor, anti-hyperlipidemic, anti-diabetic, anti-atherosclerotic, and immunomodulatory effects. These bioactivities are determined by the various structural characteristics of polysaccharides including monosaccharide composition, molecular weight, and glycosidic linkage. The widespread use of advanced analytical analysis tools has greatly improved the elucidation of the structural characteristics of C. militaris-derived polysaccharides. However, the methods for polysaccharide structural characterization and the latest findings related to C. militaris-derived polysaccharides, especially the potential structure-activity relationship, have not been well-summarized in recent reviews of the literature. This review will discuss the methods used in the elucidation of the structure of polysaccharides and structural characteristics as well as the signaling pathways modulated by C. militaris-derived polysaccharides. This article provides information useful for the development of C. militaris-derived polysaccharides as well as for investigating other medicinal polysaccharides.